Estimativa da deficiência e excedente hídrico nas bacias hidrográficas do Paranapanema III e IV e Pirapó - PR - Souza, Juliana Fontini de (2016)
The aim of the actual work was to calculate the hydro surplus and deficiency at watersheds of Paranapanema III, IV, and Pirapó, according to Thornthwaite and Mather´s hydric balance, with the aid of a computer application developed by Sentelhas et al. (1999). Data of temperature and rainfall between 1976 to 2014, were collected. Temperature data from 1976 to 2010 were collected from UDEL (University of Delaware) database´s Air Temperature and Precipitation, available at: http://www.esrl.noaa.gov/psd/data/gridded/data.UDel and from 2011 to 2014, the temperatures were collected from five weather stations belonging to: Agronomic Institute of Paraná (IAPAR), National Institute of Meteorology (INMET) and Paraná Meteorological System ( SIMEPAR). At the rainfall stations that were not possible to collect the temperature data, evaluations ere done according to Ometto´s methodology (1981). The rainfall data were collected at the Institute of Paraná Waters. The hydric balance was applied to the annual, seasonal and monthly scales to all historic series of 1976 to 2014 and the same scales for the dry year (1988) and the rainy year (2009), chosen according to the standard year´s methodology. The results show that the stations that receive the highest amounts of rainfall were the summer with 33% followed by spring with 31%.But the winter was the driest season with 16% of the total and fall to 20%. The standard year of technical pointed the years 1984, 1985, 1988 and 1991 as dry and rainy were 1976, 1983, 1990, 1998 and 2009. The other years were classified as tending to dry, tending to rainy and usual.The results of the hydric surplus and deficiency were presented using maps elaborated by the computer program ArcGis 10.2. They show that rainfall distribution is strongly attached conditioned to the dynamic regional atmospheric and the relief form, in other words, the areas that received more rain registers the biggest hydric surplus and the areas that have the smallest altimetry quotas receive the smallest volumes, therefore subjected to dry risk, presenting biggest values of deficits, and this behavior applies to all years and for all scales of analysis.